Cultivating the Foundation of Early Childhood Language Development by Communicating from the Womb - Nufus, Ajijah Sadiah; Kumala Dewi, Nurul Fitria; Rachmi, Titi (BUHUTS AL ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Humans are social creatures, where in everyday life there is interaction between humans and this interaction uses language. Language is a means of communication in interacting with other humans, so that language is important in human life. As important as in children's lives Language development includes several aspects of development, namely (Speaking, Listening, Writing and Telling Stories) (Ilmiah et al., 2022) and all these aspects are interconnected in language development as well as the development of children's language which needs to be considered from an early age even since in the womb (fetus), this study researchers focus on the development of early childhood language, stimulating children's language development can be done since the child is in the womb, namely parents can chat, read books and provide audio such as music / chanting of holy verses of the Qur'an. This is reinforced by research data (Suri Nelliraharti, 2019) , that fetuses who are often stimulated or listened to the recitation of the holy verses of the Koran are proven to be more intelligent children and cognitive nerve cells are interconnected and children become more prominent in aspects of cognitive and language development. This study applies descriptive qualitative research. The place of research is Posyandu Mawar 10 Gelam Jaya Pasar Kemis Tangerang. This research was conducted from 7-10 October 2024, and involved 15 parents who already had toddlers and were pregnant with their 2nd/3rd/4th child. This study used 3 stages of data collection, namely data reduction, data presentation and data collection. Children who are accustomed to being chatted with by their parents since they were in the womb have developed effective communication between children and parents so that children find it easier to express their feelings with verbal and non-verbal language. An emotional warm relationship is established between parents and children so that it is easier to stimulate children in each phase, especially in the development of children's language. Children's intelligence in language and cognitive development tends to be more prominent because of the interaction of chatting between the fetus and parents helping brain nerve cells connect to each other, this is assisted by consistent postnatal stimulation (Nufus, 2021) . This study focuses on parents' understanding of the stimulation of children's language development since in the womb and children who are accustomed to being chatted with since in the womb , parents in today's era have very easy access to all information but do not necessarily implement it while children grow up side by side with technology where the main stimulation is from parents.